Timing Optimization Method for Pumped Storage Plant Construction Considering Capital Expenditure Capacity Feedback - Jie Jiao; Xiaoquan Lei; Puyu He; Qian Wang; Guangxiu Yu; Wenshi Ren; Shaokang Qi (Energies)
With the extensive integration of renewable energy into the power grid, pumped storage power plants have become an essential component in the development of modern power systems due to their rapid response capabilities, advanced technology, and other beneficial features. However, high construction costs and irrational capital expenditure and construction schedules have constrained the robust and sustainable growth of pumped storage plants. Therefore, this paper proposes a pumped storage plant construction timing optimization method considering capital expenditure capacity feedback. Initially, an analysis is conducted on the factors that influence the capital expenditure costs of pumped storage power plants throughout their lifecycle. Next, the value of investing in pumped storage plants is assessed across three different aspects: economics, environment, and reliability. Finally, according to the principle of dynamic planning combined with the actual needs and capital expenditure potential of pumped storage plants, the sum of the capital expenditure effectiveness values in each stage is used as the indicator function of each stage to construct the pumped storage plants project capital expenditure timing optimization model, and a simulation analysis is carried out with Province Z as an example to verify the validity and applicability of the proposed model. The findings indicate that the suggested model is effective in balancing the implementation time of individual projects to achieve the maximum cumulative capital expenditure performance over the entire planning period.